2020
DOI: 10.35900/jjas.v3i1.2345
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Morfometrik Ukuran Tubuh Kambing Lokal Umur Pra Sapih Yang Di Pelihara Secara Tradisional

Abstract: This study aims to determine body size and body size of pre-age old goat breeds traditionally maintained in Kabila Bone District, Bone Bolango District and to find out the local goat maintenance system applied by farmers in Kabila Bone District, Bone Bolango District. The research material was local goat aged pre-age from 1 week to 10 weeks as many as 30 individuals. This study used a survey method. Retrieval of data by purposive sampling and sample determination by accidental sampling. The data obtained were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…The skull width of the male Kisar sheep was 11.31 ± 1.03 cm and 10.12 ± 0 .57 cm in the ewe. Based on the research, it is also known that the skull width of Waringin sheep is wider than that of local sheep which only has a skull width of 4.66 ± 1.03 cm for males and 3.32 ± 0.57 cm for female sheep, this statement is in accordance [12] Based on Table 7, it was found that the average body height of Waringin sheep aged 6-12 months for males was 52.18 ± 2.61 cm, for females 50.90 ± 3.32 cm, for sheep aged 12-18 months for males 52.18 ± 2.61 cm and in males aged 18-24 months, 72.50 ± 1.16 cm, females 60.60 ± 5.62 cm. The body height of local sheep aged 2 years is between 50.5 -66.5 cm, with an average of 58.29 ± 3.95 cm.…”
Section: Morphometric Characteristics Of Waringin Sheepsupporting
confidence: 54%
“…The skull width of the male Kisar sheep was 11.31 ± 1.03 cm and 10.12 ± 0 .57 cm in the ewe. Based on the research, it is also known that the skull width of Waringin sheep is wider than that of local sheep which only has a skull width of 4.66 ± 1.03 cm for males and 3.32 ± 0.57 cm for female sheep, this statement is in accordance [12] Based on Table 7, it was found that the average body height of Waringin sheep aged 6-12 months for males was 52.18 ± 2.61 cm, for females 50.90 ± 3.32 cm, for sheep aged 12-18 months for males 52.18 ± 2.61 cm and in males aged 18-24 months, 72.50 ± 1.16 cm, females 60.60 ± 5.62 cm. The body height of local sheep aged 2 years is between 50.5 -66.5 cm, with an average of 58.29 ± 3.95 cm.…”
Section: Morphometric Characteristics Of Waringin Sheepsupporting
confidence: 54%
“…The increase in body size in Kacang goats can continue to increase according to the age of the livestock and environmental conditions. Based on the results of reports from previous studies, age is a factor that can determine the growth of body size, with a presentation of 78.52% [13].…”
Section: Evaluation Of Chest Circumference In the Kacang Goat Populationmentioning
confidence: 99%
“…Faktor genetik juga dapat berpengaruh terhadap keragaman ukuran tubuh ternak. Ilham dan Laya (2020) (Tagoi KY, 2020) menyatakan bahwa seekor ternak pada dasarnya akan mengalami perubahan dimensi tubuh yang diakibatkan oleh sistem pemeliharaan, perubahan musim, dan jenis kelamin ternak. Perbedaan ukuran tubuh dari ketiga bangsa kambing perah yang diukur pada penelitian ini disebabkan oleh perbedaan laju pertumbuhan otot dan tulang sehingga terjadi perbedaan ukuran DD yang signifikan diantara ketiga bangsa kambing perah yang diukur.…”
Section: Dalam Dadaunclassified